Advantages and disadvantages of studying at IIUM - Zubairi, Ainol Madziah; Rokis, Rohaiza; Wok, Saodah; Md Ghalib, Mohd. Feham; Saidin, Aznan Zuhid; Tunku Mohd Mokhtar, Tunku Mohar; Dzulkarnain, Ahmad Aidil Arafat; Zul Kepli, Mohd Yazid; Wan Husain, Wan Rohaida (Alumni and Career Service Division, IIUM, 2013)
The monograph reports the tracer study conducted to track graduates' performance or progress after completing their undergraduate studies. This study on IIUM graduates identifies the employability of graduates from the IIUM who completed their studies in 2013. A total of 4057 graduates completed the questionnaire of IIUM Tracer Study 2013 assessing various issues related to employment and employability. It also studies the graduates' perception on Islamisation of Knowledge, graduates' perceptions on academic programme, involvements in co-curricular activities, facilities and services, teaching and learning resources at IIUM, predictors of graduates' employability among IIUM graduates and graduates' suggestions to improve quality of the Kulliyyahs' programmes.